Exceptionally potent inhibitors of fatty acid amide hydrolase: The enzyme responsible for degradation of endogenous oleamide and anandamide - Boger, Dale L. (The National Academy of Sciences, 2000)
The development of exceptionally potent inhibitors of fatty acid amide hydrolase (FAAH), the enzyme responsible for the degradation of oleamide (an endogenous sleep-inducing lipid), and anandamide (an endogenous ligand for cannabinoid receptors) is detailed. The inhibitors may serve as useful tools to clarify the role of endogenous oleamide and anandamide and may prove to be useful therapeutic agents for the treatment of sleep disorders or pain. The combination of several features—an optimal C12–C8 chain length, π-unsaturation introduction at the corresponding arachidonoyl Δ(8,9)/Δ(11,12) and oleoyl Δ(9,10) location, and an α-keto N4 oxazolopyridine with incorporation of a second weakly basic nitrogen provided FAAH inhibitors with K(i)s that drop below 200 pM and are 10(2)–10(3) times more potent than the corresponding trifluoromethyl ketones.